Changes of phytoestrogens daidzein, genistein and their glycosides daidzin and genistin and coumestrol during processing of soyabeans - J. Lojza; V. Schulzová; J. Hajšlová (Czech Journal of Food Sciences, 2004)
Phytoestrogens represent biologically active compounds showing estrogenic activity similar to that of sex hormones - estrogens. Various adverse effects such as sterility, increase of females' genitals, lost of males' copulation activity, etc. were observed in farm animals after exposure to higher amounts of fodder containing phytoestrogens. On the other side, their presence in human diet is nowadays the object of many research studies concerned with prevention of breast and prostate cancer, osteoporosis and other hormone-linked diseases by dietary intake of phytoestrogens. Soya (Glycine max) is one of the main sources of these compounds in diet. Isoflavones daidzein and genistein occurring either free or bound in glycosides are the main phytoestrogens in this food crop. Coumesterol representing coumestans is another effective phytoestrogen contained in some eddible plants. In the first part of our study, analytical method for determination of free and total phytoestrogens was developed and validated. Following steps are included: (i) acid hydrolysis (only for "total phytoestrogens" analysis), (ii) extraction with methanol/water mixture, (iii) SPE preconcentration; (iv) identification/quantification using HPLC/DAD/FLD. The aim of present study was to document the fate of phytoestrogens and their forms during household/industrial processing. As documented in our experiments the most dynamic changes of phytoestrogen levels occur during soyabeans sprouting. High levels of coumestrol even exceeding other phytoestrogens were detected on this occasion.